Предмет: Математика, автор: vovik2708

Помогите хоть что-то сделать

Приложения:

Ответы

Автор ответа: dtnth
0
что-нибудь
f'(x)=(ln(1-5x)+sqrt{7x^2+e})'=\\frac{1}{1-5x}*(-5)+frac{1}{2sqrt{7x^2+e}}*7*2x=\\frac{-5}{1-5x}+frac{7x}{sqrt{7x^2+e}}
======================
y'=(x^2e^{x^2+3x})'=2x*e^{x^2+3x}+x^2*e^{x^2+3x}*(2x+3)=\\e^{x^2+3x}x(2x^2+3x+2)
=================
y'=((1+frac{1}{x^3})^3)'=3*(1+frac{1}{x^3})^{3-1}*(0-frac{1}{x^6}*3x^2)=\\-frac{9(1+frac{1}{x^3})^2}{x^4}=-frac{9(x^3+1)^2}{x^{10}}
Похожие вопросы